2014
DOI: 10.7196/samj.7466
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional analytical study of geophagia practices and blood metal concentrations in pregnant women in Johannesburg, South Africa

Abstract: Background. Geophagia, a form of pica, has been shown to be widely practised in sub-Saharan Africa, especially among pregnant women. Objective. To assess the prevalence of geophagia and examine exposure to selected metals and associated risk factors in women attending an antenatal clinic at Rahima Moosa Mother and Child Hospital, Johannesburg, South Africa, during June and July 2010. Methods. We conducted a cross-sectional study on a convenience sample of 307 pregnant women, ranging in age from 18 to 46 years.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 18 publications
2
37
3
1
Order By: Relevance
“…Rate of consumption that varied during pregnancy from daily to casual, with occasional or casual consumption dominating is consistent with [39]. Geophagy has been reported amongst different professions [39], and it is observed not to be linked to any specific profession like in this study.…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…Rate of consumption that varied during pregnancy from daily to casual, with occasional or casual consumption dominating is consistent with [39]. Geophagy has been reported amongst different professions [39], and it is observed not to be linked to any specific profession like in this study.…”
Section: Resultssupporting
confidence: 71%
“…Studies have confirmed that geophagy during pregnancy is linked to nausea or vomiting associated with morning sickness [37], taste [37][38] influence from others [39][40] and therapeutic where clay or soil is considered like a medicament [39]. Rate of consumption that varied during pregnancy from daily to casual, with occasional or casual consumption dominating is consistent with [39].…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…Pica may have consequences like gastrointestinal disturbances; lead, mercury or arsenic intoxication; parasitic infestation; or potassium abnormalities (8). The frequency of pica varies from place to place, however, it appears to be more common in children, women, black people, people residing in rural areas and pregnant women (9). Its frequency in the United States of America ranges from 4% among men to 68% in pregnant women and 18.5% in children (10).…”
Section: Introductionmentioning
confidence: 99%
“…Although there exist beliefs about the nutritional benefits and detoxifying effects of geophagia [1] some reports indicate that ingestion of soil causes anemia [2][3]. Others present contrary view of no association between geophagia and anemia [4].…”
Section: Introductionmentioning
confidence: 99%